Effect of anti-angiogenic drugs along with chemotherapy in breast cancer treatment: review article - Najibeh Nasiri; Amir Avan; Seyed Mahdi Hassanian; Majid Khazaei (Mashhad University of Medical Sciences, 2019)
Introduction: Cancer is one of the most common causes of death in the world and breast cancer is known as the second leading cause of death in women worldwide. Breast cancer is a heterogeneous tumor; various studies have shown that angiogenesis plays an important role in progression and development of cancer. Clinical studies have been performed on the relationship between anti-angiogenic drugs along with chemotherapy in improvement of breast cancer treatment. This review article was performed with aim to evaluate the effect of anti-angiogenic drugs along with chemotherapy in breast cancer treatment. Methods: In this review study, the related articles were searched in databases of Scopus, PubMed, ISI and Google scholar by the key words including "Breast cancer", "Anti-angiogenic drug", " Chemotherapy" and "Angiogenesis" in Mesh between 2000-2018. No time limitation was considered in selection of the articles. Selection of the articles was based on use of anti-angiogenic drugs along with chemotherapy or as part of chemotherapy drugs in breast cancer treatment. At the end of study, data were analyzed qualitatively. Results: According to the studies' results, it was determined that use of anti-angiogenic drugs in improving breast cancer treatment could be more investigated. VEGF and VEGFR inhibitors have shown different clinical effects that could be due to differences in dosage, method of consumption or drug interactions. Conclusion: Although anti-angiogenic drugs have positive role in improving breast cancer treatment, since different results in doses and method of consumption of these drugs were observed in clinical trials, performing more studies in this regard is required. In general, it seems that these drugs in combination with standard chemotherapy agents could be a good candidate for treatment and increasing survival rate in breast cancer patients.